"You can smell the freedom": a qualitative study on perceptions and experiences of sex among Swedish men who have sex with men in Berlin. Issue 6 (14th June 2019) - Dennermalm, Nicklas; Ingemarsdotter Persson, Kristina; Thomsen, Sarah; Forsberg, Birger C
Abstract : Purpose: The purpose of this study was to explore the perceptions and experiences of sex among Swedish Men who have Sex with Men (MSM) in Berlin. Background: MSM are disproportionally affected by HIV. Berlin is also a key destination when looking into where Swedish MSM sero-convert, while travelling. Method: A qualitative study with semi-structured interviews using open-ended questions with participants recruited through network sampling. Data were analysed with content analysis. Participants: 15 Swedish cis-men (as in non-transgender) who have sex with men aged 25–44 years, who travelled to or were living in Berlin. To be included in the study, the participants had to be cis-MSM, Swedish citizens, spending time in Berlin and having sex in both settings. Results: For a majority of the participants, sex was the main reason for going to Berlin but cultural aspects like art and the techno scene were also important. Berlin was perceived as a sex-oriented city providing venues where respondents did not have to care about reputation and status and where social and sexual spaces co-existed side by side. This in sharp contrast to Sweden, which represented a limiting environment both in culture and what was available culturally and sexually. Conclusion: The men interviewed experienced multiple partners and had a broad sexual repertoire both abroad and at home. However, the behaviour was amplified in Berlin. The men did not alter their safer sex practice depending on if they had sex in Sweden or Berlin. The high mobility and vulnerability for HIV/sexually transmitted infection (STI) among these men highlights the need of increased access to antiretroviral treatment, pre-exposure prophylaxis for HIV and low-threshold HIV/STI testing services in Europe.